Os movimentos retóricos em introduções do gênero relatório de pesquisa científica produzido por alunos do ensino médio - Miranda, Gerciane Lima de (2022)
This paper presents an analysis of the Introduction section of research reports produced by students in the first grade of high school from a full-time school in the state network, with the main objective of analyzing formal and structural linguistic aspects present in the Introduction section of the scientific research report genre, produced in the subject Center of Work, Research and Social Practices (NTPPS). Based on the assumption that because it is a genre belonging to the academic discursive domain, the scientific research report genre has prototypical movements that belong to the macrostructure of the genre and make it to be recognized as such by community members belonging to the academic discursive domain. We seek to identify the rhetorical movements present in the Introduction section of the analyzed reports, in the light of Swales socio-rhetorical for the study of textual genres. Considering as one of the indispensable structure elements for the construction of the analyzed genre, we also seek to identify, when analyzing the Introduction of reports section, the referential cohesion strategies responsible for introduction and recovering the referent that acts as the nucleus of the theme, the object of research of each report analyzed; and the sequential cohesion strategies used to establish semantic and discursive relation between clauses, utterances or sequences in the text. We use the approach to referential cohesion of Ingedore Koch (2007), (2014), (2018), which treats cohesion as a tool for the informational and argumentative advancement of the text. We also discussed the importance of the cohesion strategies identified and analyzed in the process of continuity and textual progression. Finally, we found, through the qualitative analysis of the corpus consisting of five research reports produced by students of the first grade of high school enrolled in the NTPPS subject, that the rhetorical movements showed a presence that we can consider constant in the distribution of information in the analyzed section; and that the strategies presented by the students both for the construction of the reference chains of their research objects and for the establishment of the semantic and discursive relations established between the clauses, utterances or sequences of the text, through sequential cohesion, showed that they occupy different stages of writing development of the modality referring to the requested genre, in this case the scientific research report, as well as appropriation of the academic scientific discourse. Considering the results pointed out, we believe we provide contributions to the teaching of the Portuguese language, through the consolidation of rhetorical movements, as well as cohesion strategies for the construction of discursive textual genres belonging to the academic discursive domain.